Moral Foundations of Constitutional Thought : Current Problems, Augustinian Prospects - Walker, Graham (Book collections on Project MUSE., 2014)
Graham Walker boldly recasts the debate over issues like constitutional interpretation and judicial review, and challenges contemporary thinking not only about specifically constitutional questions but also about liberalism, law, justice, and rights. Walker targets the ""skeptical"" moral nihilism of leading American judges and writers, on both the political left and right, charging that their premises undermine the authority of the Constitution, empty its moral words of any determinate meaning, and make nonsense of ostensibly normative theories. But he is even more worried about those who.